Pathogenic mechanisms and therapeutic promise of phytochemicals and nanocarriers based drug delivery against radiotherapy-induced neurotoxic manifestations. (31st December 2022) - Iqubal, Ashif; Iqubal, Mohammad Kashif; Sharma, Sumit; Wasim, Mohd; Alfaleh, Mohamed A.; Md, Shadab; Baboota, Sanjula; Ali, Javed; Haque, Syed Ehtaishamul
Abstract: Radiotherapy is one of the extensively used therapeutic modalities in glioblastoma and other types of cancers. Radiotherapy is either used as a first-line approach or combined with pharmacotherapy or surgery to manage and treat cancer. Although the use of radiotherapy significantly increased the survival time of patients, but its use has been reported with marked neuroinflammation and cognitive dysfunction that eventually reduced the quality of life of patients. Based on the preclinical and clinical investigations, the profound role of increased oxidative stress, nuclear translocation of NF-kB, production of proinflammatory cytokines such as TNF-α, IL-6, IL-β, increased level of MMPs, increased apoptosis, reduced angiogenesis, neurogenesis, and histological aberrations in CA1, CA2, CA3 and DG region of the hippocampus have been reported. Various pharmacotherapeutic drugs are being used as an adjuvant to counteract this neurotoxic manifestation. Still, most of these drugs suffer from systemic adverse effect, causes interference to ongoing chemotherapy, and exhibit pharmacokinetic limitations in crossing the blood-brain barrier. Therefore, various phytoconstituents, their nano carrier-based drug delivery systems and miRNAs have been explored to overcome the aforementioned limitations. The present review is focused on the mechanism and evidence of radiotherapy-induced neuroinflammation and cognitive dysfunction, pathological and molecular changes in the brain homeostasis, available adjuvants, their limitations. Additionally, the potential role and mechanism of neuroprotection of various nanocarrier based natural products and miRNAs have been discussed.